Media thickness measurement of the common carotid artery - Loizou, Christos P.; Pattichis, Constantinos S.; Pantziaris, Marios; Nicolaides, Andrew N.; Georgiou, Niki; Kyriakou, Efthyvoulos (My University, 2007)
The intima-media thickness (IMT) of the common carotid artery (CCA) is widely used as an early indicator of the development of cardiovascular disease (CVD). It was proposed but not thoroughly investigated that the media thickness (MT), its composition and texture may be indicative for identifying the risk of stroke and differentiating between patients with high and low risk. In this study we present an automated method for segmentation of the media layer and measurement of its thickness in ultrasound images of the CCA. The snakes segmentation method was used, and was evaluated on 100 images against manual segmentation. The mean +/- standard deviation (sd) for the manual and the automated IMT measurements were 0.71+/-0.17 mm and 0.67+/-0.12 mm, and for the manual and the automated MT measurements were 0.25+/-0.12 mm and 0.25+/-0.11 mm respectively. There was no significant difference between the manual and the automated measurements. Further research for validating the proposed technique is required and for evaluating it in a larger sample of subjects.
Keywords: Image segmentation; Ultrasonic variables measurement; Thickness measurement; Carotid arteries; Ultrasonic imaging; Diseases; Impedance; Atherosclerosis; Measurement standards; Cardiovascular diseases; Image analysis; Image segmentation